Territorializing Indigeneity and Powwow Markets - Gagnon, Blaire O. (Anthropologica, 2013)
North American powwows are presented by organiz ers and presumed by society at large to be Native events. Re search has rarely considered the processes by which powwows become places or the role of territorialization in that process. This article examines the socio-spatial practices powwow or ganizing committees employ to construct powwows and their arts and crafts markets as places from undifferentiated space and the responses to these practices. I suggest that powwow committees construct powwow space as a form of sovereign political space from which they can manage relations with mul tiple constituencies and in which contemporary conceptions of Nativeness are negotiated.